Development of linear regression model for tile waste generation in Malaysian construction industry / Siti Hafizan Hassan … [et al.] - Hassan, Siti Hafizan; Abdul Aziz, Hamidi; Abdul Hamid, Mohd Samsudin; Mohd Nasir, Siti Rashidah; Mohamed Noor, Suhailah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2019)
The effect of unmanageable construction waste is an unstable land settlement and groundwater pollution. In addition to environmental pollution, construction waste could incur construction cost. The most construction waste is the material used at sites and tile is also a part of the waste generated in construction. The objectives of this study are to determine the tile waste generated in construction stages and linear regression analysis for the amount of tile waste generated. The method used in this study was the Linear Regression Model. The regression model established in the sample data reported an R2 value of 0.793; therefore, the model can predict approximately 79.3% of the factor (area) of tile waste generation. The linear regressions can be applied as tools to predict the tile waste generated at construction sites and help the contractor to track the sources of missing waste.